Silício nos aspectos fisiológicos e produção de mudas de maracujazeiro amarelo sob salinidade hídrica - Bezerra, Fabiano Simplicio (2020)
The cultivation of yellow passion fruit has stood out in the tropical fruit sector; however, its yield may be impaired due to the damage caused by salinity. In view of this, it is necessary to point out techniques that mitigate such damages, such as silicate fertilization to mitigate the negative effects of excess salts in irrigation water. In this sense, this research was divided into two chapters. The first chapter aimed to evaluate the effect of silicon doses on mitigating the effects of salinity of irrigation water on the formation of yellow passion fruit seedlings. In the second, the objective was to investigate silicon in the physiology of yellow passion fruit seedlings under salt stress. The experimental design was in randomized blocks, with five doses of silicon (0; 29; 100; 171 and 200 mg dm-3) and five electrical conductivities of irrigation water (0.3; 0.9; 2.4; 3.9 and 4.5 dS m-1), with four replications, generated from the Central Composite Box matrix. In the first chapter it was observed that the silicon dose 40.3 mg dm-3 with water of 1.0 dS m-1 provided an increase of 1.5 % in leaf area compared to the absence of silicon. The effect of silicon on relieving salt stress is attributed to the drastic decrease in na+ concentration in the aerial part of salt-stressed plants. The silicon dose 199.4 mg dm-3 attenuates those made of salinity of irrigation water in yellow passion fruit seedlings, allowing the use of water with salinity of up to 1.41 dS m-1. For the second chapter, the maximum value in the maximum photochemical efficiency of the PSII photosystem (Fv/Fm) (0.77 quantum electrons-1) was verified with the supplementation of 199.7 mg dm-3 silicon under salinity of 4.4 dS m-1, corresponding to an increase of 3.2% at Fv/Fm at 60 DAE, signaling that the photosynthetic apparatus of the seedlings remains intact, that is, they do not present damage by photoinhibition in the reaction center of photosystem II, confirming the beneficial effects of silicon in attenuating the damage of salinity in a water with a high level of salts. The silicon dose of 199.6 mg dm-3 attenuates the salinity of irrigation water of 4.4 dS m-1, allowing increase of 5.2% in the chlorophyll index ratio a/b at 60 DAE.